National e-cigarette survey (NECS) 2016: prevalance, pattern and perception regarding e-cigarette and vape use among Malaysian adults - Nik Mohamed, Mohamad Haniki (Institute for Public Health, Ministry of Malaysia and International Islamic University Malaysia, 2016)
The e-cigarette is defined as a battery-operated device which vaporizes a nicotine solution into a form of an inhalable aerosol.